The power of scripture political biblicism in the early Stuart monarchy between representation and subversion - Pečar, Andreas 1972-; Voort, Jozef van der; Walcoff Neuheiser, Jennifer (New York Berghahn Books, 2021)
"In England, from the Reformation era to the outbreak of the Civil War, religious authority contributed to popular political discourse in ways that significantly shaped the legitimacy of the monarchy as a form of rule as well as the monarch's ability to act politically. The Power of Scripture casts aside parochial conceptualizations of that authority's origins and explores the far-reaching consequences of political biblicism. It shows how arguments, narratives, and norms taken from Biblical scripture not only directly contributed to national religious politics but also left lasting effects on the socio-political development of Stuart England"--
"Abbreviated translation of a study that was originally published ten years ago in German. Unfortunately, the chapters on the history of the Reformation and on political biblicism in Scotland have not been included in the English version of the text."--Acknowledgements
Literaturverzeichnis: Seite 223-256, Index
Keywords: Church and state -- England -- History -- 16th century; Church and state -- England -- History -- 17th century; Bible and politics; Reformation -- England; England -- Church history -- 16th century; England -- Church history -- 17th century